The Effect of Mind Mapping Learning Strategy in Science to the Fifth Grade Students’ Learning Outcomes - Yolanda Devita N; Agustiningsih Agustiningsih; Fajar Surya Hutama (Pancaran Pendidikan, 2018)
The research was conducted in SDN Gebang 04 Jember in order to investigate a significant influence of the use of mind mapping learning strategy to the learning outcomes of the fifth grade students in learning science with earth structures as the topic. This research was an experimental research. The research design was pre-experimental utilizing intact-group comparison. The subjects of the research were as many as 44 students consisting of 22 students of class VA and 22 students of class VB. The data was collected from post-test. The research results showed that the post-test average score of the experimental class was higher than that of the control class. The average score of the experimental class was 83.54 while the average score of the control class was 74.23. Due to the difference between the two scores, independent test was administered. From the test it was obtained that tcomputation = 4.195 with significance value of p = 0.000. Because the coefficient was less than 0.05, null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The results indicated that there was a significant influence of mind mapping learning strategy towards students’ learning outcomes.